Urinary Incontinence Prevalence during Pregnancy: the Ethiopian perspective - Kebede, Eskinder; Kassaye, Getu (Ethiopian Journal of Reproductive Health, 2020)
ABSTRACT Urinary incontinence (UI) is a common but under-reported problem among women globally. Information on the prevalence and health burden of UI in Ethiopia is unknown. Measuring the prevalence of these symptoms has been difficult because of lack of uniform nomenclature and standardized tool. This study aimed to establish the prevalence of urinary incontinence and its determinants among pregnant women in Addis Ababa, Ethiopia. This was a cross-sectional study in which the International Consultation on Incontinence criteria qualified Questionnaire was administered in July 2015, to 333 consenting pregnant women aged 15 to 42 years who were attending Antenatal care at, tertiary Hospitals, in Addis Ababa, Ethiopia. Of the three hundred thirty three pregnant women 82(24.6%) reported Urinary Incontinence. Thirty eight (11.4%) reported stress urinary incontinence only, 15(4.5%) reported urge incontinence only and 29(8.7%) reported mixed incontinence during the preceding month (8% had moderate or severe symptoms). Sixty nine percent of these had not consulted a health care professional. The determining factor for prevalence of UI was the mode of delivery. Of the pregnant women who practiced C/S the prevalence of UI was lower than those women whose mode of delivery was vaginal (AOR: 0.46:95%CI (0.22, 0.98). This study showed that many pregnant women in Ethiopia suffer in silence from a variety of lower urinary tract symptoms. There is need to create awareness among women with symptoms as nearly two third (64%) of those with daily episodes of urinary incontinence do not seek help. Health care providers must build their capacity to recognize, investigate and manage lower urinary tract morbidities in pregnancy Keywords: Lower urinary tract symptoms, Pregnancy, ICI, the Leister Urinary Symptom Questionnaire, Addis Ababa, Ethiopia